Trust in management, communication, Islamic work ethics and readiness for change a mediating effect of organisational commitment - Nurul Iza, Adnan (2014)
Rapid social and environment changes have posed a challenge to public service in ensuring that the programmes and activities undertaken meet the needs and expectations of the stakeholders, including the people in particular. Hence, civil servants must always be ready and responsive to the demands of this constant change through the current initiatives of the Government Transformation Programme (GTP). Both civil servants and government organisations need to work in hand to ensure the success of the transformation. Previous studies showed that the readiness for change is influenced by various organisational and individual factors, such as trust in management, communication and Islamic work ethics. Therefore, this study aimed at investigating the relationship between trust in management, communication, Islamic work ethics and readiness for change within ministries in Malaysia. In addition, this study is also conducted to evaluate the mediating effect of organisational commitment on the relationship between trust in management, communication, Islamic work ethics and readiness for change. Respondents for this study are Administrative and Diplomatic Service Officers (PTD) (Grades 48 and 52) who work in the ministries in Malaysia. All the hypotheses are tested using AMOS 21.0 and based on structural equation modelling (SEM) analysis, it is shown that trust in management, communication and Islamic work ethics have a significant effect on readiness for change. Besides that, organisational commitment is found to fully mediate the relationship between trust in management and communication with readiness for change, while partially mediating the relationship between Islamic work ethics and readiness for change. On the whole, the findings of this study provide a positive impact on change management planning, which ultimately helps in ensuring more effective GTP implementation.